Prevalence and severity of depression among people residing in flood affected areas of Kerala - Jom Thomas, Jose; Prakash, B.; Kulkarni, Praveen; Narayana Murthy, M. R. (International Journal Of Community Medicine And Public Health, 2019)
Background: The world is witnessing significant change in its climate leading to an increase in natural disasters. Kerala state of India recently witnessed its worst Monsoon rainfall in the century. Floods have significant effects on mental health. Screening of psychological problems is necessary in the background of recent floods in Kerala. So this study was done with the objectives to assess the prevalence of depression in the flood affected people of Kerala and to assess the severity of depression among people residing in flood affected areas of Kerala. Methods: Cross sectional study was done four weeks after flood. Individuals aged ≥15 years residing in flood affected areas were included and people not willing to participate were excluded. Purposive sampling was done and 306 participants were studied. Participants were assessed by interview technique using PHQ9 questionnaire. Data was analysed using SPSS-22. Descriptive statistics like percentage were applied. Inferential statistical tests like chi-square test were applied for association. Results: Among the participants 48% showed symptoms of depression. 28.10 % were mildly depressed, 12.74% were moderately depressed, 5.56% had moderately severe and 1.63% had severe depression. Maximum prevalence of depression was observed in geriatric age group. Conclusions: A significant amount of people residing in flood affected areas showed signs and symptoms of depression. An urgent intervention is therefore required to improve mental health status of the flood affected individuals.